2005
DOI: 10.1186/1475-2891-4-3
|View full text |Cite
|
Sign up to set email alerts
|

The treatment of migraines and tension-type headaches with intravenous and oral niacin (nicotinic acid): systematic review of the literature

Abstract: BackgroundMigraine and tension-type headaches impose a tremendous economic drain upon the healthcare system. Intravenous and oral niacin has been employed in the treatment of acute and chronic migraine and tension-type headaches, but its use has not become part of contemporary medicine, nor have there been randomized controlled trials further assessing this novel treatment. We aimed to systematically review the evidence of using intravenous and/or oral niacin as a treatment for migraine headaches, tension-type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 31 publications
(29 reference statements)
0
25
0
Order By: Relevance
“…The same vitamin B combination with a 1 mg dose of folic acid was not superior to placebo 185 . According to a systematic review 186 in which nine open studies were identified, niacin (nicotinic acid or vitamin B 3 ) might also have a prophylactic effect in migraine, but randomized controlled trials are lacking.…”
Section: Prophylactic Nutraceuticalsmentioning
confidence: 99%
“…The same vitamin B combination with a 1 mg dose of folic acid was not superior to placebo 185 . According to a systematic review 186 in which nine open studies were identified, niacin (nicotinic acid or vitamin B 3 ) might also have a prophylactic effect in migraine, but randomized controlled trials are lacking.…”
Section: Prophylactic Nutraceuticalsmentioning
confidence: 99%
“…Riboflavin in combination with CoQ 10 has been shown to reduce neurological episodes associated with migraine headaches (505). The combined approach augments complex I activity and has been used in clinical trials to demonstrate their combined effectiveness for preventing migraine attacks (459). Niacin has also been used as a supplement to boost mitochondrial energy metabolism by increasing substrate availability to complex I; in this way it might act to deter=reduce migraine headache (459).…”
Section: E Mitochondria and Dietary Supplementsmentioning
confidence: 99%
“…The combined approach augments complex I activity and has been used in clinical trials to demonstrate their combined effectiveness for preventing migraine attacks (459). Niacin has also been used as a supplement to boost mitochondrial energy metabolism by increasing substrate availability to complex I; in this way it might act to deter=reduce migraine headache (459). Clearly, the efficacies of these approaches remain to be resolved, their side effects remain under scrutiny, and they are limited by the fact that some studies have failed to make any association of migraine headache or dietary supplements with specific mitochondria deficits.…”
Section: E Mitochondria and Dietary Supplementsmentioning
confidence: 99%
“…Because it can dramatically increase blood flow and circulation within the brain, picamilon is used as a nootropic [2]. Also used for the treatment of depression, anxiety, and migraine [3], picamilon works by crossing the blood-brain barrier, after which it is hydrolyzed into GABA and nicotinic acid [4]. In addition, picamilon has extremely low toxicity and shows no allergenic or carcinogenic properties [1].…”
Section: Introductionmentioning
confidence: 99%